Adherence to Canada's Food Guide recommendations among Alberta's multi‐ethnic youths is a major concern: findings from the WHY ACT NOW project. Issue 5 (24th May 2018) - Kolahdooz, F.; Nader, F.; Daemi, M.; Jang, S. L.; Johnston, N.; Sharma, S.
Abstract: Background: Dietary habits formed during youth may result in the development of obesity and chronic diseases in adulthood. We aimed to determine the frequency of the consumption of foods and beverages and the degree of adherence to Canada's Food Guide recommendations among multi‐ethnic youths. Methods: Participants were recruited from 12 schools in the Edmonton, Alberta area by use of posters, school newsletters and advertisements. A 30‐item food frequency questionnaire was administered by a trained interviewer to assess dietary intake in a convenience sample of 557 (328 females and 229 males) youths aged 11–23 years; for the purpose of the present study, only the 14–18 years age group was considered in the analysis. Participants were divided by sex and self‐identified ethnicity into four groups [Indigenous, African & Middle Eastern (AME), Asian, and European]. Statistical analysis of the data was undertaken using t ‐tests, Welch's analysis of variance and Games‐Howell tests. P < 0.05 was considered statistically significant. Results: Vegetables and Fruit recommendations were the least likely to be followed, with 90.7–96.8% of participants in all groups not consuming the recommended number of servings day –1 . The mean frequency of fruit consumption was lower among Indigenous youths compared to Asian youths (0.90 versus 1.37 times day –1 ). A greater proportion of males than females (55.9% versus 44.3%) did not meet the minimum recommendations for Meat and Alternatives ( P = 0.016). The percentage of youths not adhering to recommendations for Milk and Alternatives was 81.7% for Indigenous, 73.3% for AME, 78.6% for Asian and 63.5% for European youths. Indigenous youths more frequently consumed potato chips and soft drinks compared to other ethnic youths. The most frequently consumed beverage was milk (1.25 times day –1 ). Conclusions: The majority of youths did not consume minimum daily recommended servings of Vegetables and Fruit, Milk and Alternatives, and/or Meat and Alternatives food groups. Evidence‐based dietary interventions and public health strategies are needed.